Metabolic and inflammatory risk reduction in response to lipid-lowering and lifestyle modification in the medically underserved individuals - Michael P. Chu; Gina Many; Daniel A Isquith; Susan McKeeth; Jayne Williamson; Moni B Neradilek; Patrick Colletti; Xue-Qiao Zhao (Elsevier, 2021)
Introduction: Medically underserved (US) populations have an increased level of atherosclerotic cardiovascular disease (ASCVD) risk, however, few studies investigated ASCVD risk reduction in US. Methods: Of 217 subjects with ApoB ≥120 mg/dL and carotid atherosclerosis (≥15% stenosis by ultrasound) enrolled in the Carotid Plaque Composition by MRI (CPC) study between 2005 and 2011, US (n=33) was defined as those without adequate healthcare insurance, while AS (n=184) included those with adequate healthcare coverage. All subjects received atorvastatin-based lipid therapies and lifestyle intervention for 2 years. Metabolic and inflammatory risk factors were compared between AS and US. Results: At baseline, compared to AS, US displayed higher levels of metabolic and inflammatory risk including systolic blood pressure (140±27 vs. 131±18 mmHg, p=0.04), fasting glucose (125±59 vs. 102±22 mg/dL, p=0.03) and fasting insulin (39±33 vs. 28±20 µU/dL, p=0.03) which resulted in higher insulin resistance (HOMA-IR 2.2±0.4 vs. 1.3±0.1, p=0.03), and hsCRP (5.6±1.5 vs. 2.8±0.2 mg/L, p=0.03). Over 2 years of intervention, US and AS showed similar reductions in LDL-C (-10.7% vs. -16% per year, p=0.2), triglycerides (-16.7% vs. -15.9% per year, p=0.4), and hsCRP (-0.11% vs. -0.04% per year, p=0.1). However, US continued to show significantly higher levels of fasting blood glucose (115±6.0 vs. 101±2.0 mg/dL, p=0.03) and HOMA-IR (1.9±0.2 vs. 1.5±0.1, p=0.047), and hsCRP (3.9±0.7 vs. 1.9±0.2 mg/L, p<0.001) than AS following 2 years of interventions. Conclusions: US displayed higher ASCVD risk than AS at baseline and over 2 years despite similar reductions following the intervention. These findings highlight the unmet needs for improved intervention strategies and implementation methods for ASCVD risk reduction in US. Clinical Trial Registration: NCT00715273 at ClinicalTrials.gov